MODEL OPTIMISASI NONLINIER JARINGAN PIPA GAS DENGAN PERCABANGAN - Rumlawang, Francis Y. (PATTIMURA UNIVERSITY, 2007)
Gas transmission system has a branch to costumer area that affects to flow rate, gas pressure, and pipe diameter. This paper discusses optimization of this transmission system. Optimum gas pressure and pipe diameter was found by minimizing cost objective function subjects to panhandle A and panhandle B constrain function. Steepest Descent method which is combined with Rangekutta methods is use to determine the optimization process. The result shows that the pipe branches affect the optimization variables.